Standardised Evaluation of Shanghai-Hangzhou High-Speed Maglev Project - Cui, Yong; Tritschler, Stefan; Martin, Ullrich; Mo, Fan (Promet - Traffic&Transportation, 2019)
In recent years, high-speed maglev systems have received renewed attention once again. However, a systematic and transparent approach to evaluate high-speed maglev projects does not currently exist, which could be an obstacle for their application, even with technical success. In Germany, the Standardised Evaluation is applied as a basis for decision making regarding the public funding of projects. It should be implemented for all investments of urban public transport projects with a value of more than € 25 million. In this paper, the economic evaluation for the Shanghai-Hangzhou maglev project is carried out with the Standardised Evaluation. One of the most important contributions of this work is to demonstrate the applicability of Standardised Evaluation for high-speed maglev projects. With the Standardised Evaluation, the evidence of macroand microeconomic benefit can be presented in a transparent and systematic way. The result can be used to prove the project’s profitability and to rank different projects or project alternatives.